The Effect of Road Infrastructure and Electricity Infrastructure on Economic Growth - Maximiliane Leonora Cornelia Hukom; Marcha Matitaputty; Simson Natten (Public Policy : Jurnal Aplikasi Kebijakan Publik dan Bisnis, 2026)
This study examines the effects of road and electricity infrastructure on economic growth in West Seram Regency, Indonesia. A quantitative approach was employed using a field survey supported by a literature review. Primary data were collected through structured questionnaires, while secondary data were obtained from official government publications. The data were analyzed using multiple linear regression analysis. The findings demonstrate that road and electricity infrastructure jointly exert a significant positive influence on regional economic growth. Improvements in transportation and electricity infrastructure enhance accessibility, facilitate the movement of goods and services, increase economic productivity, and strengthen regional connectivity. This study contributes to the limited empirical evidence on the complementary role of road and electricity infrastructure in promoting economic growth within island regions. The findings also provide practical insights for regional governments in designing integrated infrastructure investment policies to support sustainable economic growth and reduce regional development disparities.